The effect of coffee-eucalyptus deglupta agroforestry systems over water contamination with nitrates in micro-watershed from the south zone of Costa Rica - Renderos Durán, Reina V. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (costa Rica), 2001